Analysis of Employee Performance at the Sumedang Employment BPJS - Nining Kurniasih; Salsabila, Salsabila, (SINTESA, 2023)
The research focuses on the performance of employees at the Sumedang Employment BPJS. The purpose of this study was to determine employee performance, performance problems and efforts to overcome performance problems at the Sumedang Regency Employment BPJS office. This research uses qualitative research methods. In analyzing the research data using Milles andHuberman model analysis starting from data collection, data reduction, datapresentation and data conclusions. Based on the results of observations, interviews and data analysis, it is concluded that employee performance is sufficient but not optimal. BPJS Employment Sumedang employees experience decreased work motivation, still make mistakes in terms of writing reports, inputting data, calculating reports, employee accuracy in their work is not good enough, still procrastinate their work and there is still miscommunication. Efforts made to overcome employee performance problems by conducting briefing activities, holding weekly evaluations, morning exercises once a week, family gatherings.